"Am I qualified to be a language tester?": Understanding the development of language assessment literacy across three stakeholder groups. (April 2021) - Yan, Xun; Fan, Jason
Recent investigations into language assessment literacy (LAL) suggest that stakeholder groups might differ in interests, needs, and expectations in assessment practice, resulting in different LAL profiles. This qualitative study furthers this line of research by examining the effect of contextual and experiential factors on the LAL profiles and development of different stakeholder groups. Semi-structured interviews were conducted among 20 participants from three stakeholder groups in China, including language testers, EFL teachers, and graduate students. Results indicate that LAL profile differences existed at both group and individual levels. At the group level, language-testing researchers and students demonstrated greater familiarity with assessment concepts than did EFL teachers; however, EFL teachers were able to understand and link those concepts with assessment practices. At the individual level, each participant experienced a different LAL development process; yet, these processes share some common patterns. Based on these patterns, a common LAL development model for all stakeholders is proposed. Assessment training should consider the resources in stakeholders' assessment contexts and their experiences in assessment development, use, and research and develop realistic expectations in LAL development for different stakeholders.